CHALLENGES IN VITAMIN D ANALYSIS - Serteser, Mustafa; Coskun, Abdurrahman; Inal, Tamer C.; Unsal, Ibrahim (SCIENDO, 2012)
Vitamin D is an important determinant for the regulation of calcium and phosphorus levels and mineralization of the bone. The most reliable indicator of vitamin D status is the measurement of plasma or serum 25OH-D concentration. Several studies reported discrepancies between the results of assays. These high variabilities in 25OH-D measurements are due to used assay technologies and lack of standardization against the reference materials. Different assays have been employed for the measurement of 25OH-D levels: Competitive Protein Binding Assays, immunoassays, direct detection methods. Choosing an assay platform is important both for clinical laboratory professionals and researchers, and several factors affect this process. Recently, liquid chromatography and tandem mass spectrometry is an alternative method to traditional assays and provides higher specificity and sensitivity than many assays

therefore, it has been suggested as a candidate reference method for circulating 25OH-D3. Standardization of methods for the quantification of 25OH-D by using the human-based samples would reduce the inter-method variability. The best way for laboratories to demonstrate the accuracy of their results is by participating in the external quality assessment scheme. Standardization of the assays is also required to provide clinicians with the accurate tools to diagnose hypovitaminosis. In addition, assay-specific decision limits are needed to define appropriate thresholds of treatment.
Keywords: 25 Hydroxy Vitamin D; assay; standardization; external quality control; LC-MSMS